Proteomic study of peripheral blood lymphocytes of rabbits with severe burn and Pseudomonas aeruginosa sepsis - Zeng, Ji-zhang (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2009)
OBJECTIVE: To study the effect of severe burn and Pseudomonas aeruginosa sepsis on the proteomics of lymphocytes (LCs) of rabbits